2011
DOI: 10.1177/1049909111418636
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Cancer Pain and Quality of Life in Patients Newly Admitted to Wuhan Hospice Center of China

Abstract: To evaluate the relationship between pain and quality of life (QoL) in patients newly admitted to Wuhan Hospice Center, China. A total of 1,634 patients were analyzed in this retrospective study. A Numerical Rating Scale and Chinese-QoL instrument were used to assess pain score and QoL, respectively. Most patients experienced moderate to severe pain, which significantly impaired QoL. The pain was significantly correlated with appetite, mood, sleep, fatigue, pain intensity, daily activity, side effect, general … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
49
0
5

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 36 publications
2
49
0
5
Order By: Relevance
“…In this study, increasing pain severity scores directly correlated with greater interference in both physical and psychological functions, which is in line with existing evidence . Moderate to severe interference from pain on sleep was experienced by the majority of patients.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this study, increasing pain severity scores directly correlated with greater interference in both physical and psychological functions, which is in line with existing evidence . Moderate to severe interference from pain on sleep was experienced by the majority of patients.…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, those who rated sleep interference as moderate or severe experienced more intense pain than those who suffered mild sleep interference. These results are not unexpected, as sleep disturbance has been shown to be significantly associated with pain in cancer patients . An analysis of associations between pain of varying intensities and specific QoL measures in cancer patients found a clear relationship between least pain and insomnia, indicating that even minor pain affects sleep quality .…”
Section: Discussionmentioning
confidence: 62%
“…Deng et al () found that pain was an important factor that negatively impacted not only in the physical but also in the emotional aspects of HRQOL but the literature points out several factors, other than pain, which may explain the low HRQOL. It is possible that the frequent hospitalisations and treatment‐related side effects, invasive procedures, emotional distress, environmental factors and symptoms (nausea, fatigue) lead to a decrease in the social, emotional and cognitive ability and consequently a decrease in HRQOL.…”
Section: Discussionmentioning
confidence: 99%
“…The levels of alkaline phosphatase or lactic dehydrogenase that were higher than the upper limit of the normal range were considered abnormal. The pain levels were classified as none (0), mild (1-3), moderate (4-6), and severe (7-10), based on a numerical rating scale (NRS)[20], [21].…”
Section: Methodsmentioning
confidence: 99%